PENGARUH KEPUASAAN KERJA DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN PT BANK SAHABAT SAMPOERNA JAKARTA - Iwan Kurniawan Subagja; Arief Syah Safrianto (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
This study aims to analyze 1) the effect of job satisfaction on employee performance at PT Bank Sahabat Sampoerna KCP Kelapa Gading, 2) the effect of work loyalty on employee performance at PT Bank Sahabat Sampoerna KCP Kelapa Gading, 3) the effect of job satisfaction and job loyalty towards employee performance at PT Bank Sahabat Sampoerna KCP Kelapa Gading. The data used in this study are primary data with a research instrument in the form of a questionnaire. The population in this study were employees at PT Bank Sahabat Sampoerna KCP Kelapa Gading. The sample is 48 respondents. The saturated sampling technique and the analytical tool used in this study is simple and multiple linear regression. The results showed: 1) job satisfaction affected the performance of employees at PT Bank Sahabat Sampoerna KCP Kelapa Gading, 2) work loyalty affected the performance of employees at PT Bank Sahabat Sampoerna KCP Kelapa Gading, 3) job satisfaction and work loyalty affected the performance of employees at PT Bank Sahabat Sampoerna KCP Kelapa Gading.